2014
DOI: 10.1016/j.juro.2013.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Tissue Remodeling Urinary Biomarkers before and after Mid Urethral Sling Surgery for Stress Urinary Incontinence

Abstract: Objective Urinary biomarkers were measured from women at baseline and 1 post-surgery for stress urinary incontinence (SUI) and associations with clinicodemographic covariates and outcomes were analyzed. Methods Pre- and post-surgery urine specimens from 150 women were assayed for inflammatory biomarkers (TNF-α, IFN-γ, IL-1β, IL6, IL10, IL12p70, IL17, NGF) and tissue remodeling biomarkers (collagenase activity, MMPs-1, 2, 9, 13, N-telopeptide cross-linked collagen (NTx), EGF, HB-EGF). Paired t-tests compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
0
5
0
6
Order By: Relevance
“…A recent study by Chai et al 13 looked at various urinary biomarkers before and after midurethral sling surgery for stress urinary incontinence. The urinary markers after continence surgery trial studied urinary NGF values in 150 women with stress urinary incontinence before and 1 year after midurethral sling surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Chai et al 13 looked at various urinary biomarkers before and after midurethral sling surgery for stress urinary incontinence. The urinary markers after continence surgery trial studied urinary NGF values in 150 women with stress urinary incontinence before and 1 year after midurethral sling surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was no significant difference between plasma levels of markers of collagen synthesis such as pro-collagen type 1-N pro-peptide, MMP-9 and vitamin C in patients with POP and/or SUI and controls. In another study, urinary collagenase assay of factors including MMP-1, -2 and -9 was the optimum pre-operative predictor of mid-urethral sling outcome in women with SUI, and revealed negative correlation with urethral closure pressure (20,21). Recent genotypic studies have identified molecular markers of dysfunction of the supportive pelvic floor connective tissue, with genetic polymorphism of MMP-1 and -9 identified in women with POP compared with controls (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…O resultado do nosso estudo difere de outra série que demonstrou níveis urinários diminuídos de MMP-1 em pacientes obstruídos, apresentando uma tendência a ser negativamente correlacionado com a obstrução infravesical, apesar do autor não evidenciar significância estatística (Chai et al, 2014). Contudo, alguns autores demonstraram, em analise tecidual, que um modelo de OIV em ovelhas resultou no desenvolvimento de fibrose vesical e acúmulo de colágeno e matriz extracelular (Peters, 1997).…”
Section: Discussionunclassified
“…Esses resultados estão em concordância com os encontrados em séries que avaliaram os níveis desses biomarcadores em pacientes com SBH e HD (Tyagi et al, 2010;Bouchelouche et al, 2004;Bouchelouche et al, 2006;Alkis et al, 2015;Chai et al, 2014 (Tyagi et al, 2010;Alkis et al;2016;Chai et al, 2014 (Tyagi et al, 2010). A presença de EGF aumentado na urina é sugestivo de reparação tecidual e fibrose em pacientes com SBH e OIV (Tyagi et al, 2010;Chai et al, 2014 (Abrams, 2005). Em alguns casos, os aspectos objetivos e subjetivos podem não se correlacionar.…”
Section: Discussionunclassified
See 1 more Smart Citation